PERSEPSI SISWI KELAS X TATA BUSANA TENTANG KOMPETENSI MEMBUAT POLA TEKNIK KONSTRUKSI DI SMKN 3 SUNGAI PENUH - Harmaida, Julita; Ramainas, Ramainas; Ernawati, Ernawati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
The aim of this research is to describe how the students perception about pattern drawing tools, measuring, drawing construction technic pattern, broken pattern technic according to the design. The kind of this research is quantitative descriptive. It use total sampling. Data collection did by using questionnaire with Likert scale, spread to all respondents that have been passed validation and realibility test.version The result shows that the students perception about the drawing tools is high (77,1%). Measuring is high (79,5%). Producing construction technic is very high (84,4%). Broken pattern accoring to the design is very high (87,3%). The students perceptiion about the competens in producing construction technic patter is very high (83,65%).